Editorial on Bioethics and Educational Institutes, Vol 11 No 3 - Rhyddhi Chakraborty (Bangladesh Journal of Bioethics)
In the past few years, Bioethics, the branch of applied ethics, has been widely established as a discipline, as a value framework, a framework of principles, a tool, as a medium for practical skill development to help individuals understand complex moral, social, legal, environmental issues in medicine, clinical and health research. As a discipline, bioethics invite interdisciplinary deliberation and draws people from all sectors of society to engage in discussion. Bioethics also serves as the potential medium for greater community engagement and participation involving both professionals and non-professionals.